Madelung's Deformity of the Wrist—Current Concepts and Future Directions - Babu, Satish; Turner, Joseph; Seewoonarain, Sheena; Chougule, Sanjay (Journal of Wrist Surgery, 2019)
Madelung's deformity of the wrist arises from premature closure of the medial and volar aspect of the distal radial physis. True Madelung deformities reveal the presence of a “Vickers” ligament which is a short, volar, radioulnar ligament. Clinically, patients report increasing deformity, pain, and poor range of motion. Radiological features include increased radial inclination, volar tilt of the distal radius, and a positive ulnar variance. Surgical intervention usually comprises either a “Vickers” ligament release and distal radius physiolysis or a radial dome osteotomy. In future, EOS Imaging could aid diagnosis by providing more detailed images of the deformity while minimizing radiation exposure. Furthermore, three-dimensional printing and computer-navigated deformity correction could revolutionize management by facilitating simulation training, expediting surgery, and reducing intraoperative error.
Keywords: Madelung; wrist; DRUJ; deformity; congenital